A term (write his hadith )is written by Imam Ibn Uday, may Allah forgive him, in his Al kamil book on weak men - Hamadh, Odai Jasem; Hamad, Maha Azam (Journal of Tikrit University for Humanities, 2023)
The research dealt with the study of the phrase (writes his hadith) by Al-Hafiz Ibn Uday - may God have mercy on him - in his complete book on weak men and its concept and interpretation. It was used by critics and it became clear that this phrase is one of the most ambiguous phrases for Imam Ibn Uday, and accordingly, it is not possible to know the ruling on the narrator about whom Ibn Uday said (he writes his hadith) except after studying the statements of the imams of criticism about him.